Perioperative comparison of uniportal versus multiportal video-assisted thoracoscopic surgery for complex segmentectomy of the lower lung lobe - Xinyu Wang; Yuming Wang; Min cao; Yujie Fu; Wenbiao Pan; Qing Ye; Xiaojing Zhao; Zhiyong Sun (BMC Surgery)
Abstract Background Resection of basal segmentectomy through uniportal video-assisted thoracoscopic surgery (U-VATS) is technically challenging for thoracic surgeons. Compared with multiportal VATS (M-VATS), the safety and feasibility of U-VATS for complex segmentectomy of lower lung lobe need further validation. In this study, we aimed to compare the perioperative outcomes of U-VATS with M-VATS in the treatment of complex segmentectomy of lower lung lobe for stage IA lung cancer. Methods We conducted a retrospective cohort study of 168 patients (116 U-VATS and 52 M-VATS) undergoing complex lower lobe segmentectomy for stage IA NSCLC from January 2021 to May 2023. The demographics of the enrolled patients were collected and propensity score matching (PSM) was used to reduce the heterogeneity of baseline characteristics. Perioperative outcomes were compared between the two groups. Results After matching, 50 cases were yielded in each group. There was no 30-day postoperative mortality and conversion to open in both groups. The U-VATS exhibited shorter postoperative hospital stays (P = 0.034) and a trend toward reduced postoperative drainage (P = 0.081) compared to the M-VATS group. Pain score on postoperative day 2 in the U-VATS group was lower than M-VATS group (P = 0.004). There were no significant differences in resection margins, operation time and postoperative complications between the two groups. Conclusions U-VATS provides comparable perioperative safety and efficacy to M-VATS for complex lower lobe segmentectomy, with advantages in accelerated recovery and reduced postoperative pain. U-VATS complex segmentectomy of lower lung lobe is a safe and feasible technique for experienced thoracic surgeons, which deserves support and popularity.